The association between appendectomy and increased invasion of ascending colon cancer: a retrospective study involving 880 patients - Xu Sun; Rui Li; Wen Zhao; Dingchang Li; Guanglong Dong (World Journal of Surgical Oncology)
Abstract Background Ascending colon cancer is a subtype of colorectal cancer (CRC), the most common malignant tumor globally. The appendix has been considered to be a vestigial organ and appendectomy is the most routine management of acute appendicitis. However, limited studies have examined the association between appendectomy and the invasion of ascending colon cancer. Methods In this retrospective study, 880 cases of ascending colon cancer were selected. The preoperative and postoperative clinicopathological features were retrospectively studied. Logistic regression was performed and the propensity score matching (PSM) method was used to adjust for confounding factors. Results In total of 880 patients, 133 patients had a history of appendectomy. Patients with a history of appendectomy exhibited a higher proportion of number of lymph node metastasis (LNM) (P = 0.047), T4 stage (P = 0.025), N1 stage (P = 0.037), N2 stage (P = 0.045), M1 stage (P = 0.008), stage III (P = 0.047), and stage IV (P = 0.003). The model following PSM revealed that a history of appendectomy was associated with an increased risk of LNM and M1. In 747 patients without a history of appendectomy, 568 patients (76.0%) were diagnosed with chronic appendicitis pathologically. Patients with chronic appendicitis had significantly smaller tumor sizes (P = 0.012), reduced lymphovascular invasion (LVI) (P = 0.001), fewer poorly differentiated tumors (P = 0.012,), a lower number of LNM (P = 0.020), less frequent T4 stage tumors (P = 0.023), and a decreased incidence of N2 stage disease (P = 0.035). Conclusions Appendectomy is associated with a higher aggressiveness of subsequent ascending colon cancer, particularly regarding LNM. Chronic appendicitis has been linked to a decrease in tumor invasion of ascending colon cancer.